Taxonomy and distribution of Cheilolejeunea larsenii Mizut. (Marchantiophyta, Lejeuneaceae), with special reference to three new synonyms - Shu, L.; Cheng, X.F.; Daniels, A.E.D.; Yong, K.T.; Zhu, R.L. (2015)
Cheilolejeunea exinnovata E.W. Jones, a rare and poorly known liverwort from Africa and Brazil, C. ghatensis G. Asthana, S.C. Srivast. & A.K. Asthana, previously endemic to India, and C. adnata (Kunze ex Lehm.) Grolle var. autoica Gradst. & Ilk.-Borg. reported only from French Guiana are proposed as new synonyms of the Asian Cheilolejeunea larsenii Mizut., so far known only from China and Thailand. Cheilolejeunea larsenii is characterized by its rounded leaf apex, a small and strongly inflated leaf lobule that possesses a distinctively long and unicellular lobule tooth, and an absence of gynoecial innovations. A detailed description, taxonomic notes, new localities, distribution map, and illustrations of C. larsenii are provided.